Activation of chicken intestinal intraepithelial lymphocytes by oral administration of Mycobacterium phlei* - SREEKUMAR, E; DAS, SUBRATA K (The Indian Journal of Animal Sciences, 2014)
Mycobacterial organisms have long been used as potentiators of immune response by parenteral route. In this study, Mycobacterium phlei, a commensal organism was used as an oral immunomodulator in chickens. Orally administered heat-killed M phlei (0 10 mg/ bird in 2-week-old chickens altered the phenotype and functional properties of intestinal intraepithelial lymphocytes (IELs). The number of CD8+ cells in IEL population increased and the lymphocyte transformation test by MTT colorimetric assay showed significant enhancement in experimental group. The non-specific cytotoxicity ofÂ of IELs against BHK-21 tumour targets and virus infected autologous peritoneal macrophages were also increased in experimental birds administered with M. phlei. Thus oral administration of heat-inaetivuted M. phlei activated IELs of chicken.